Reduction Of Graphene Oxide Nanosheets By Natural Beta Carotene And Its Potential Use As Supercapacitor Electrode - K. F., Chong; M. Zaid, Rubaiyi; Teo, Ellie Yi Lih; Chong, Fui Chin; Ng, Eng Poh
A green, non-toxic and eco-friendly approach for the reduction of graphene oxide (GO) nanosheets using natural b-carotene is reported. The FTIR spectroscopy and thermogravimetric analyses reveal the oxygen scavenging property of b-carotene successfully removes oxygen functionalities on GO nanosheets. Complete GO reduction is achieved within 16 h with 10 mM b-carotene as confirmed by the UV spectroscopy results. The high resolution transmission electron microscopy images provide clear evidence for the formation of few layers of graphene nanosheets. Furthermore, the mechanism of GO reduction by b-carotene has been proposed in this study. The electrochemical testing shows good charge storage properties of b-carotene reduced GO (142 F/g at 10 mV/s; 149 F/g at 1 A/g in Na2SO4), with stable cycling (89%) for up to 1000 cycles. The findings suggest the reduction of GO nanosheets by b-carotene is a suitable approach in producing graphene nanosheets for supercapacitor electrode.